The Physics of Climate Change: A Book Review - Arafat, Yasir (Pusbindiklatren Bappenas, 2025)
Climate change is inevitable. It stands as one of the triple planetary crises, along with pollution and biodiversity loss, impacting countries worldwide. People across the globe have a responsibility to achieve Goal 13 of SDGs, which emphasizes the urgency for immediate and concerted efforts to address climate change and its multifaceted consequences (Juniper, 2021). The adverse effects of climate change exacerbate existing issues such as poverty, food insecurity, and public health crises, thereby undermining global progress towards sustainable development. Consequently, this issue has gained significant political and technocratic attention, necessitating coordinated efforts to address its challenges. Significantly, the response to the challenge of climate change is grounded in a robust scientific framework. The 2021 Nobel Prize in Physics reaffirmed the importance of science-based policy by honoring a group of scientists for their groundbreaking research on Earth's climate system. This recognition underscores the irrelevance of the question,